POST-OCCUPANCY EVALUATION STUDY: OCCUPANT’S PERCEPTION VS. OCCUPANCY SURVEY - Mundo-Hernández, Julia; Valerdi-Nochebuena, Cristina; Sosa-Oliver, Jorge (European Scientific Journal, ESJ, 2015)
This paper presents the results of an assessment of a higher education building located in the city of Puebla in Mexico. The research carried out is a post-occupancy evaluation study of a building built forty years ago but still very heavily used. The building is covered by four concrete shell structures joined together by a translucent dome. A focus group and a questionnaire provided us the views of the building users regarding environmental factors, aesthetics and functionality of the building. People’s perceptions have been compared with the results of an occupancy survey, which has shown how people is using the building, peak usage times and space occupancy. Improvements to the building are suggested based on the data obtained. The main aim of this research is to improve the interior environment of the building while learning from it in order to design new good quality and sustainable education buildings.